(untitled) (Nusantara Medical Science Journal, 2017)
ABSTRACT Introduction: The role of Total Antioxidant Capacity (TAC) is the cumulative effect of all the antioxidants found in the blood and body fluids. Objective: to know the total antioxidant status in patients with HIV and CD4 stage I and stage IV. Methods: Thirty-four patients with HIV who are divided into two groups, one was HIV patients with stage I and group 2 was HIV patients with stage IV. Checking of total antioxidant status and CD4 in both groups. Results: There was no significant difference in total antioxidant status in HIV oenderita stage I and stage IV. There are significant differences in the levels of CD4 HIV patients with stage I and stage IV. There is a relationship between total antioxidant status and CD4 in patients with HIV. Conclusion: the higher the CD4 count, the higher the total antioxidant capacity in patients with HIV. Keywords : CD4, Patients HIV, Total Antioxidant Capacity